Optimaslisasi Supplay Chain Management Produk Olahan Ikan Hasil Tangkap Di Kabupaten Labuhanbatu - Ayu Intan Pratiwi; Melati Melati; Siti Aisyah (Universitas Labuhanbatu, 2022)
Being a maritime country, Indonesia has a wealth of potential marine products. Fishery is a human endeavor involved in the administration of aquatic products. Fisheries activities in Indonesia start from pre-production and continue through production, processing, and marketing. There are many groups of fishermen in North Sumatra Province, especially in the coastal area of Labuhanbatu Regency, Panai Hulu Regency, which has a supply chain due to fish catches. The purpose of this study is to find out how the supply chain due to fish catches in the downstream area of Panai Hulu and Panai, Labuhanbatu Regency is carried out. Using primary data from interviews and field observations, this research method uses descriptive qualitative research. Based on the research findings, there are differences in supply chains and optimization of fishing in Labuhanbatu Regency, especially in Panai Hulu District. MSMEs that are the target of this research are MSMEs engaged in fish processing in Labuhanbatu Regency. Various types of fish, such as anchovies, puffer fish, squid, crab, tuna and skipjack tuna, have been caught.